2011
DOI: 10.1111/j.1365-2265.2011.03987.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between androgens and cardiovascular risk factors in a young population

Abstract: Our results suggest that SHBG is independently associated with HOMA-IR, adiponectin, hs-CRP and triglycerides. A gender difference in these associations is observed. Further studies are needed to elucidate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The inverse relationship between TT and CRP was also found in KIHD study among nondiabetic middle‐aged men and another study of type 2 diabetes . In addition, a recent study in a young Middle‐Eastern population demonstrated negative associations of both TT and SHBG with CRP, although the study sample size was small . Of notice, our study, coupled with these previous studies, involved relative young‐ to middle‐aged population.…”
Section: Discussionsupporting
confidence: 76%
“…The inverse relationship between TT and CRP was also found in KIHD study among nondiabetic middle‐aged men and another study of type 2 diabetes . In addition, a recent study in a young Middle‐Eastern population demonstrated negative associations of both TT and SHBG with CRP, although the study sample size was small . Of notice, our study, coupled with these previous studies, involved relative young‐ to middle‐aged population.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with other observational studies serum testosterone was negatively associated with some markers of inflammation (Bonithon-Kopp et al, 1988;Brand et al, 2012;Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Yang et al, 1993;Zhang et al, 2013). This study adds by considering an additional biomarker of androgen activity, AAG, which was not associated with lower values of any of the inflammatory markers considered, but was associated with higher fibrinogen as well as with hemoglobin as would be expected of an androgen.…”
Section: Discussionsupporting
confidence: 91%
“…The available evidence from these RCTs generally shows little effect of testosterone therapy on CRP (Aversa et al, 2010;Frederiksen et al, 2013;Kapoor et al, 2007;Nakhai-Pour et al, 2007;Ng et al, 2002), white blood cell count (Kalinchenko et al, 2010) or fibrinogen (Smith et al, 2005), although one RCT reported testosterone decreased CRP (Kalinchenko et al, 2010) among a subset of men. Larger observational studies among men usually, but not always, report serum testosterone inversely associated with CRP (Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Nakhai Pour et al, 2007;Zhang et al, 2013), white blood cell counts and/or its differentials (Brand et al, 2012;Haring et al, 2012;Tang et al, 2007) and fibrinogen (Bonithon-Kopp et al, 1988;Haring et al, 2012;Yang et al, 1993). Experimental and observational evidence may differ for a number of reasons: the small size of most RCTs of testosterone therapy, differences in the action of exogenous and endogenous testosterone, serum testosterone acting as a marker of health status or serum testosterone not capturing all androgen activity (Labrie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mean hsCRP of the low testosterone group was 3.2 +/-1.0 mg/dL and of normal testosterone group was 1.9 +/-0.9 mg/dL. In the study performed by Gannagé-Yared et al, (11) they studied 201 men and found that Total Testosterone was inversely associated with serum hsCRP and BMI. The study of Schneider HJ et al (12) concluded that obesity, metabolic syndrome, and acute inflammation was associated with hypogonadal testosterone levels.…”
Section: Testosterone and Hscrpmentioning
confidence: 93%